IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH ENGLISH SONG IN SEVENTH GRADE JUNIOR HIGH SCHOOL - Siti Mardiah Zurriatun; Zihori Maulida; Masyudi Masyudi; Rospin Hidayati (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2024)
This study aims to determine the increase in students' vocabulary mastery by using songs. This research was conducted using Classroom Action Research (CAR). The subjects of this study were students in class VII D of Abul Barokat Islamic Middle School for the 2023/2024 academic year, a total of 28 students. The purpose of this research is to improve students' vocabulary mastery through English songs. This research was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data is collected through qualitative and quantitative data. Qualitative data obtained by interviews and observation results. Then, quantitative data were obtained from the students' vocabulary scores from the pre-test, post-test. Based on the results of this study, it showed that there was progress in students' vocabulary mastery, as seen from the average pretest score of 66.07, the average posttest 1 score was 72.14, and the average posttest score. cycle 2 is 78.93. In addition, there were 5 students (18%) who passed the KKM on the pretest. Whereas in cycle 1 there were 15 students (54%) who passed the Minimum Completeness Criteria (KKM), and it was obtained in the post test cycle 2 that there were 24 students (86%) who passed. Criteria (KKM), so that success criteria are achieved. Then, the results show an increase and a positive response in the learning process of teaching vocabulary through English songs. Furthermore, the results of observations and interviews show that students are motivated in the teaching and learning process when using this English song.